2004
DOI: 10.1177/1051228404266267
|View full text |Cite
|
Sign up to set email alerts
|

Correlating Brain Atrophy With Cognitive Dysfunction, Mood Disturbances, and Personality Disorder in Multiple Sclerosis

Abstract: Neuropsychological impairment is a common feature of multiple sclerosis. Affected patients often have deficits in information-processing speed and memory and exhibit psychopathological states such as depression. A minority of patients have rarer affect/mood disorders such as euphoria sclerotica and pathological laughter/crying. Neuropsychological impairment is a major predictor of low quality of life, unemployment, and caregiver distress. Studies evaluating correlations between neuropsychological impairment an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
78
1
6

Year Published

2005
2005
2012
2012

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 131 publications
(88 citation statements)
references
References 99 publications
(92 reference statements)
3
78
1
6
Order By: Relevance
“…After normalization to the TICV, using Eq. [1], the mean upper cervical cord CSA in controls was 77.97 Ϯ 0.95 mm 2 . There was no statistically significant difference (P ϭ 0.670) in mean normalized CSA between the males (78.48 Ϯ 1.49 mm 2 ) and females (77.65 Ϯ 1.25 mm 2 ).…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…After normalization to the TICV, using Eq. [1], the mean upper cervical cord CSA in controls was 77.97 Ϯ 0.95 mm 2 . There was no statistically significant difference (P ϭ 0.670) in mean normalized CSA between the males (78.48 Ϯ 1.49 mm 2 ) and females (77.65 Ϯ 1.25 mm 2 ).…”
Section: Resultsmentioning
confidence: 90%
“…The relative contribution of each of these pathological features to long-term neurological deficit is unknown. Axonal loss, however, is thought to be an important factor contributing to long-term cumulative persistent dysfunction (1,2). It is also thought to contribute to atrophy of the CNS (3).…”
mentioning
confidence: 99%
“…However there is evidence to suggest that whole grey and white matter volume, as compared with lesion burden, is more closely related to neuropsychological performance and neuropsychiatric symptoms [2,3]. Our investigations of total white and grey matter volume in patients with type 1 diabetes revealed a relationship between cerebral white matter volume and cognitive performance [4].…”
Section: Wmhs White Matter Hyperintensitiesmentioning
confidence: 70%
“…The reader is referred to several recent detailed reviews on the relationship between CNS atrophy in MS and cognitive impairment, 166 physical disability, 167 disease course, 167 mood disturbances, 166 and quality of life. 167 Losseff et al 168 showed that progression of brain atrophy, but not T2-hyperintense lesions over 18 months, was related to deterioration of EDSS score.…”
Section: Atrophy Of the Cnsmentioning
confidence: 99%
“…166 One of the first studies conducted in this area demonstrated that linear measures of brain atrophy (bifrontal span, bicaudate span, and third ventricle width) were significantly correlated with cognitive impairment. 176 Subsequent work confirmed the close relationship between cognitive impairment and atrophy in central brain regions, measured by corpus callosum atrophy, 177 the bicaudate ratio, 178 and enlargement of the lateral ventricles.…”
Section: Atrophy Of the Cnsmentioning
confidence: 99%